2021
DOI: 10.1039/d1ra02887a
|View full text |Cite
|
Sign up to set email alerts
|

On the key role of aluminium and other heteroatoms during interzeolite conversion synthesis

Abstract: The crucial roles of aluminium in driving and controlling interzeolite conversion, a useful catalyst synthesis protocol, are put under scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 194 publications
(425 reference statements)
1
47
0
Order By: Relevance
“…The ability to synthesize zeolites with isomorphically substituted heteroatoms is specific to both the element and framework of interest, 16 where many combinations can only be synthesized after prohibitively long synthesis times. 4 It has been suggested that the addition of heteroatom precursors to zeolite syntheses alters crystallization kinetics by modifying physicochemical properties of the growth mixture 17 or facilitating the formation of crystal structures that are thermodynamically less stable owing to heteroatom incorporation. 18 Investigating these hypotheses, however, is nontrivial since complex synthesis media and nonclassical crystallization mechanisms obfuscate attempts to identify causal relationships between synthesis parameters and growth kinetics or properties of zeolites/zeotypes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to synthesize zeolites with isomorphically substituted heteroatoms is specific to both the element and framework of interest, 16 where many combinations can only be synthesized after prohibitively long synthesis times. 4 It has been suggested that the addition of heteroatom precursors to zeolite syntheses alters crystallization kinetics by modifying physicochemical properties of the growth mixture 17 or facilitating the formation of crystal structures that are thermodynamically less stable owing to heteroatom incorporation. 18 Investigating these hypotheses, however, is nontrivial since complex synthesis media and nonclassical crystallization mechanisms obfuscate attempts to identify causal relationships between synthesis parameters and growth kinetics or properties of zeolites/zeotypes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tetrahedrally coordinated aluminum sites are balanced by extra-framework cations, often hydrogen (i.e., Brønsted acid sites), where the concentration and siting of Al atoms can strongly influence catalyst performance and stability. , Zeolites can also be synthesized with a wide range of framework compositions, referred to as zeotypes (or zeolite isostructures) when tetrahedral sites (T-sites) are occupied by “heteroatoms”, which are elements other than Si and Al. Heteroatom substitution with diverse species has garnered significant interest in recent years as a method to enhance zeolite propertiesmost notably the nature and strength of Brønsted and/or Lewis acid sites . For example, tin, hafnium, and zirconium have been incorporated into the *BEA structure for applications in biomass conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have suggested that memory of the seed persists throughout dissolution and nucleation of the daughter zeolite, 64−69 it has been demonstrated that dissolved species may be oligomers lacking a high degree of local order. 56,70,71 The dissolved species can alter nucleation in ways that are not completely understood, such as promoting the emergence of nanosheets on the surfaces of amorphous precursors (Figure 2) that develop into self-pillared pentasils (SPPs). 18 When the seed (parent) and final product (daughter) are two different zeolite structures, this is termed an interzeolite transformation (IZT), which is discussed in section 3.…”
Section: Seed-assisted Synthesismentioning
confidence: 99%
“…There have been several review articles written on topics of SAS, IZT, and zeolite synthesis that provide in-depth descriptions of synthesis techniques, material properties, and zeolite performance in different applications. In this Perspective, we provide a conceptual overview of SAS pathways and highlight recent breakthroughs in the use of seeds to achieve novel materialsnotably nanosized and hierarchical zeolites. Within the context of seed-assisted methods, we provide a synopsis of IZT and propose ways to explain (or potentially predict) trends in nucleation under different synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The mechanism of IZC remains incompletely understood, and is likely to differ between examples. [19] In the majority of cases, the parent and daughter structures have common building units (CBUs), such as small rings and cages, suggesting a pathway where the CBUs prepared in the dissolution step facilitates rapid, directed crystallisation. [20] There is little direct evidence for this, however, and there are cases where there are no CBUs between parent and daughter.…”
Section: Introductionmentioning
confidence: 99%